FAKTOR – FAKTOR KECEMASAN SISWA DALAM PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Harum Fitriyani; arif budiman (JCOSE Jurnal Bimbingan dan Konseling, 2021)
Since March 2020 all education sectors have implemented learning activities at home or often referred to as offline, with the covid 19 pandemic, many changes have occurred, especially in the world of education, a lot, one of which is important in learning achievement, between IQ and EQ. IQ is 20% while 80% is intelligence. The purpose of this research is to find out aspects of distance learning in the midst of the covid-19 pandemic. what causes the level of intelligence to increase compared to before the Covid-19 pandemic This research uses a quantitative descriptive method. This research was carried out at Mts Mahadut Tholabah, Tegal district with a total of 50 respondents in class viii.